ANALISIS POTENSI KEBANGKRUTAN KEUANGAN PERUSAHAAN MAKANAN DAN MINUMAN YANG LISTED DI PT. BURSA EFEK JAKARTA - Bambang Sucahyo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2003)
The economic crisis since mid 1997 has internally affected the performance of manufacture companies. Short term foreign loans in foreign currency that can be prolonged have increased the demand for foreign currency especially the US dollar, and has resulted a depreciation of rupiah value more than 80%. This further yielded the performance failure   and financial bangkruptcy potentials.This study aimed at testing the usage offinancial ratios to determine whether a company belongs to the financial bangkruptcy potential group or otherwise. Further-more, considering tehe supposedly different condition and performance of manufacture industries before and during the crisis, this study also aimed at determining the performance of a company with and that without thefinancial bangkruptcy potential.Bangkruptcy has been investigated and can be predicted with reference to the company financial peiformance indicator, namely thefinancial ratios. However, considering that the tight competetion of the business world, the size of performance has developed with the entrance of market competetion ratio. Ratio, in this case is the capability of a company to survive in an industrial environment, which is quantified by the market share yield compared with the market size of his competitors.This study compared two periods  of financial  bangkruptcy potential predictions, namely that prior   to  the  economic  crisis  in lndonesia  (1994  - 1996)  and  that  during  the economic  crisis  (1997  -  1999).  The factor,   cluster and discriminant analysis were applied to the go public food and beverage industries at the Jakarta Stock Exhange. The discriminant analysis or the Z-score method proved effective in measuring the peiformance  in multivariate way and in grouping it. By the SPSS social statistical version 10.0, the discriminant analysis arranging the ratios into given discriminant functions, and base on the function, the sample cases were put in the given groups. if the final  ratio multiplication showed higher Z-score the case was categorized having no bangkruptcy potential. Otherwise, the case was grouped as having the bangkruptcy potential.The discriminant analysis showed that the first hypothesis was accepted. Prior to the crisis (1994    1996), factor   debt ratio and net profit margin developed the discriminant function and simultaneously determined the classification of as a group with or without bangkruptcy potential. Jn this function, net profit margin factor is dominant part that determinate a grouping of cases, and it showed that a company survival were determined by the management in measure sales producing net profit. The hit ratio of discriminant function was 98 %, showing that the precision of the classification was relatively high.During crisis period (1997 1999), the important factors in the discriminant function were debt ratio, followed current ratio, total asset turn over, and market share. It showed that during crisis, the survival of a company was determinated by management tofind the fund added to invest oppurtunity. The discriminant function had hit ratio 94,1%, that showed the classification accurancy 94,1%. From the ratio or factor comparison use in the both fun ction of the two analysis period, the two hypothesis showed a difference in ratio role to determinate the bangkruptcy potential classification for two different periods.It was also revealed that in the a both analysis periods the cutting score or Z score was null. This means that in term of discriminant function score a case was negative or smaller than Z score, the case was categorized as having the bangkruptcy potential. Othenvise, if the discriminant junction was positi ve or bigger than Z score, the case will be categorized as having no bangkruptcy potential.